Two new species of Amphinemura (Plecoptera: Nemouridae) from Yunnan, China, with the redescription of A. triramia (Wu, 1962) - Li, Weihai; Yang, Ding (Zootaxa, 2008)
Two new species in the family Nemouridae, Amphinemura interrupta sp. nov. and A. nigritubulata sp. nov., are described from Yunnan, China. Amphinemura triramia (Wu, 1962) is re-described and re-illustrated based on fresh material from the same locality. Their relationships with close relatives are discussed.